A U.S. Analysis of the Macro- and Micro-Economics of Family Formation: Marrying in the Great Recession and Prior Post-Industrial Recessions - C. Soledad Espinoza (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
With restricted-use data from the U.S. Census Bureau, I conduct an analysis of the macro- and micro-economic determinants of marrying. Based on observations across a broad segment of calendar years (from 1978 to 2010), I examine the measures of the national unemployment rate for males, national recession indicators, and micro-level proxies for earning power. The analysis focuses on comparing the marrying patterns of the non-recession years of the 2000s to the distinct U.S. recession periods of the adjacent Great Recession (2008-09), the adjacent early 2000s recession (2001-2003), and the earliest observed recession period, the 1980s (1980-82). The data include time-constant demographic variables and marital, fertility, education, and earnings life histories merged from the SIPP survey and federal administrative sources. Using ordinary logit modeling with weighted specifications, I perform regression analyses based on constructed event history data for separate models of men and women. Among both college-educated men and women, I find a marrying advantage in each period but the relation is not increasingly positive in each subsequent recession. Among college-educated women, earnings emerge as having a positive effect on marrying but the effect is not consistently positive in the subsequent recessions. Regarding college educated men, earnings are consistently observed to have a positive effect on marrying in each recession and non-recession period.
Conference: 2014 Annual Population Association of America (PAA) Meeting, May 1-3
Keywords: D1; 330; Household economics; marriage; recession; education; earnings; earning power; Household Economics; Marriage; Education; Profit